Effects of Community Factors on Access to Ambulatory Care for Lower-Income Adults in Large Urban Communities - E. Richard Brown; Pamela L. Davidson; Hongjian Yu; Roberta Wyn; Ronald M. Andersen; Lida Becerra; Natasha Razack (SAGE Publishing, 2004)
This study examines the effects of community-level and individual-level factors on access to ambulatory care for lower-income adults in 54 urban metropolitan statistical areas in the United States. Drawing on a conceptual behavioral and structural framework of access, the authors developed multivariate models for insured and uninsured lower-income adults to assess the adjusted effects of community- and individual-level factors on two indicators of access: having a usual source of care, and having at least one physician visit in the past year. Several community factors influenced access, but they did so differently for insured and uninsured adults and for the two measures of access used. The findings of this study confirm that public policies and community environment have measurable and substantial impacts on access to care, and that expanded public resources, such as Medicaid payments and safety-net clinics, can lead to measurable improvements in access for vulnerable populations residing in large urban areas.